Analysis of the Failure of Islamic Political Parties in Gaining Votes in Indonesia General Elections - Susdarwono, Endro Tri (Langgas: Jurnal Studi Pembangunan, 2023)
This study aims to analyze the failure of Islamic political parties to gain votes in general elections. This analysis is based on a hypothesis testing procedure, namely whether the proportion of failure of Islamic political parties in gaining votes in general elections is caused by constant or not constant factors (in the sense that they are caused by something significant or by design). The approach in this study uses a quantitative descriptive method using the hypothesis testing method through the khai-square distribution (X2). Based on the procedure of testing the hypothesis, this study concludes that the null hypothesis which states that the proportion of Islamic political parties that fail is constant and therefore the cause is purely chance factors (chance factors) is accepted.